The Development of Students’ Executive Functions Through Cognitively Challenging Physical Activity Games: Practical applications for Physical Education - Kolovelonis, Αθανάσιος; Goudas, Μάριος (Inquiries in Physical Education and Sport, 2025)
The aim of this paper is to present implementation guidelines for cognitively challenging physical activity games aiming at enhancing students’ executive functions in physical education. First, a new approach of designing physical activity programs focusing on promoting students’ physical activity and cognitive development jointly is presented. Next, the concept of executive functions is analyzed and the three principles of cognitive engagement are described. Then, theoretical and empirical evidence regarding the effects of cognitively challenging physical activity games is presented. The last part of the paper includes guidelines for physical education teachers for the implementation of cognitively challenging physical activity games. Practical suggestions with specific working examples regarding the development and adaptation of games and activities in order to become cognitively challenging are also included.